Standardized airway wall thickness Pi10 from routine CT scans of COPD patients as imaging biomarker for disease severity, lung function decline, and mortality - Kahnert, Kathrin; Jörres, Rudolf; Kauczor, Hans-Ulrich; Alter, Peter; Trudzinski, Franziska; Herth, Felix; Jobst, Bertram; Weinheimer, Oliver; Nauck, Sebastian; Mertsch, Pontus Jeremias Paul; Kauffmann-Guerrero, Diego; Behr, Jürgen; et al. (Therapeutic advances in respiratory disease, 2023)
Background:Chest computed tomography (CT) is increasingly used for phenotyping and monitoring of patients with COPD. The aim of this work was to evaluate the association of Pi10 as a measure of standardized airway wall thickness on CT with exacerbations, mortality, and response to triple therapy.Methods:Patients of GOLD grades 1?4 of the COSYCONET cohort with prospective CT scans were included. Pi10 was automatically computed and analyzed for its relationship to COPD severity, comorbidities, lung function, respiratory therapy, and mortality over a 6-year period, using univariate and multivariate comparisons.Results:We included n?=?433 patients (61%male). Pi10 was dependent on both GOLD grades 1?4 (p?=?0.009) and GOLD groups A?D (p?=?0.008); it was particularly elevated in group D, and ROC analysis yielded a cut-off of 0.26?cm. Higher Pi10 was associated to lower FEV1 % predicted and higher RV/TLC, moreover the annual changes of lung function parameters (p?
Gesehen am 21.04.2023